Role of Rho-kinase Inhibitor and hrsACE2 in COVID-19 Patients Management - Wilson Halim; Bryan Gervais de Liyis; Cokorda Istri Intan Dalem Sukawati (Indoscholar, 2022)
The Renin-angiotensin system (RAS) plays an important role in the SARS-CoV-2 infection through Angiotensin-converting enzyme 2 (ACE2). Human recombinant soluble ACE2 (hrsACE2) has been shown to act as a competitive interceptor for SARS-CoV-2 by preventing the binding of viral particles to the ACE2. In addition, Rho-kinase inhibitors have been proven to suppress SARS-CoV-2 infection through inhibition of the Rho-associated protein kinase (ROCK) pathway. The combined effect of hrsACE2 and Rho-kinase inhibitor increases the activity and levels of ACE2 in protection through the Ang1-7 MasR, Ang1-9, and other mechanisms of protection. This literature review is done by searching journals with “COVID-19”, “ACE2”, “hrsACE2”, “Rho- kinase inhibitor”, and “ROCK pathway” as well as Boolean logic “AND” and “OR”. Relevant journals are used as references to compile systematic writing. Based on research results, hrsACE2 and Rho-kinase inhibitors have been clinically proven to protect tissue through the elevated level of ACE2 by the mechanism of Rho-kinase inhibitor, which increased Ang1-7 MasR concentration that gives vasodilatation, anti-proliferative, anti-inflammation, and anti-fibrotic effect. Rho-kinase inhibitors significantly reduce the number of infected cells by SARS-CoV-2 in COVID-19 patients. The potential of the combination therapy of Rho-kinase inhibitor and hrsACE2 therapy can be an efficient therapeutic solution for COVID-19 patients so that further research can be carried out in the future.